Pengembangan Media Aplikasi Microsoft Powerpoint untuk Pembelajaran Tematik secara Daring pada Kelas V Tema Ekosistem di SDN 5 Kota Bengkulu - Vivi Oktavia; Irfan Supriatna (JURIDIKDAS, 2023)
This study aims to produce thematic learning media online in grade V SD. This research is a Research and Development (R&D) research by modifying the ADDIE model which is carried out until the third stage, namely Analysis, Design, and Development. The development process is carried out by conducting expert validation and small group testing (teacher and student responses). This media was validated by media experts, material experts, and linguists who were then revised and then responded to by 3 teacher respondents and 6 student respondents. The data analysis technique used qualitative descriptive analysis of the results of expert validation and comments from expert validation and small group test, as well as descriptive statistical analysis of the small group test. This research produces Microsoft Powerpoint media for online thematic learning in class V with the theme of Ecosystems, with the results of validation from media experts, material experts, and linguists that this media is categorized as feasible as online thematic learning media, the percentage of teacher responses is 95.83. % in the very practical category, and the results of student responses of 93.33% in the very practical category. So, from the research that has been carried out, it can be concluded that the Microsoft Powerpoint application media can be categorized as a very good and practical learning media and can be used in online thematic learning.